Flexor digitorum superficialis muscular activity is more reliable than mentalis muscular activity for rapid eye movement sleep without atonia quantification: A study of interrater reliability for artifact correction in the context of semiautomated scoring of rapid eye movement sleep without atonia. Issue 9 (12th April 2021) - Cesari, Matteo; Heidbreder, Anna; Bergmann, Melanie; Holzknecht, Evi; Högl, Birgit; Stefani, Ambra
Abstract: Study Objectives: To evaluate interrater reliability for artifact correction in the context of semiautomated quantification of rapid eye movement (REM) sleep without atonia (RWA) in the mentalis and flexor digitorum superficialis (FDS) muscles. Methods: We included video-polysomnographies of 14 subjects with apnea–hypopnea index in REM sleep (AHIREM ) < 15/h and 11 subjects with AHIREM ≥ 15/h. Eight subjects had isolated REM sleep behavior disorder. A validated algorithm (www.osg.be ) automatically scored phasic and "any" EMG activity in the mentalis muscle, and phasic EMG activity in the FDS muscles. Four independent expert scorers performed artifact correction according to the SINBAR (Sleep Innsbruck Barcelona) recommendations. Interrater reliability for artifact correction was computed with B-statistics. The variability across scorers of four RWA indices (phasic mentalis, "any" mentalis, phasic FDS and SINBAR—i.e. "any" mentalis and/or phasic FDS–EMG activity indices) was computed. With Friedman tests, we compared B-statistics obtained for mentalis and FDS muscles, and the variability of the RWA indices. Influence of AHIREM and REM sleep behavior disorder (RBD) diagnosis on the RWA indices variability was evaluated with linear regressions. Results: Interrater reliability for artifact correction was higher in the FDS than in the mentalis muscle ( p < 0.001). Phasic FDS activity was minimally affected by artifacts. Accordingly, the phasic FDS EMG activity index had the lowest variability across scorers ( p < 0.001). Variability across scorers of the RWA indices including the mentalis muscle increased with AHIREM and was independent from RBD diagnosis. Conclusions: Due to the consistently found low number of artifacts, phasic FDS activity is a reliable measure of RWA.